2018
DOI: 10.1177/1464420718780890
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of short and straight carbon nanotubes on dispersion state and static/dynamic mechanical properties of woven glass fibre-reinforced polymer laminates

Abstract: This study reports about the dispersibility of short, straight and pristine multi-walled carbon nanotubes (pCNTs) in epoxy and their effectiveness on the mechanical properties of three-phased GF/epoxy/pCNT laminates. These nanotubes were produced by arc discharge method and had an average aspect ratio (l/d) of 100. Glass fibre-reinforced polymer samples with four different weight fractions of these nanotubes (0.5, 1.0, 1.5 and 2.0 wt.% of the total matrix system) were fabricated and tested for their thermo-mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 67 publications
(106 reference statements)
1
18
0
Order By: Relevance
“…They showed that incorporation of 0.5 wt% nano‐silica exhibited the maximum enhancement in tensile strength as well as higher elongation at break (higher ductility) compared to other specimens. Singh and Gaurav [ 27 ] investigated the tensile properties of GFRE polymer composite filled with MWCNTs. Their study revealed that tensile strength improved, and Young's modulus decreased as the MWCNT contents were increased from 0.5 to 1.5 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that incorporation of 0.5 wt% nano‐silica exhibited the maximum enhancement in tensile strength as well as higher elongation at break (higher ductility) compared to other specimens. Singh and Gaurav [ 27 ] investigated the tensile properties of GFRE polymer composite filled with MWCNTs. Their study revealed that tensile strength improved, and Young's modulus decreased as the MWCNT contents were increased from 0.5 to 1.5 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] As per the literature review, the optimum weight percentage of nano fillers is 0.2 to 2 wt%, which ensures improved tribo-performance while retaining or even improving other mechanical properties. [20][21][22][23][24][25][26] Singh and Gaurav [27] studied the mechanical and thermomechanical properties of GFRE composites filled with multi-walled carbon nanotubes (MWCNTs) (0.5, 1.0, 1.5, 2 wt%). They concluded that the addition of MWCNTs upto 1.5 wt% facilitates enhancement in tensile strength and glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Glass fibers are stiffer than the adjacent matrix, and upon loading the apparent modulus gap causes considerable strain difference instigating high shear forces in the fiber-matrix interface. 33 Magnitude of the shear force developed on the fiber/matrix interface largely depends upon the stress magnitude; where high shear forces are generated in the fiber/matrix interface when the specimens are loaded at high stresses causing fractures mostly dominated by fiber pullouts. On the contrary, samples loaded at low stresses undergo fiber breakage rather than pullouts, mostly due to low shear stresses acting on the fiber/matrix interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…These cracks require a large number of cycles to propagate and the samples experience high fatigue life. 33 Larger cracks that eventually propagate in fewer cycles create a large plastic zone ahead of the advancing cracks. While these advancing cracks propagate in the matrix, they leave behind intact fibers, which bridge the cracks.…”
Section: Resultsmentioning
confidence: 99%
“…[22][23][24][25] As per the literature review, the optimum weight % of nanofillers is in a range of 0.2 to 2 wt.%, which ensures improved tribo-performance while retaining or even improving other mechanical properties. 9 Singh and Gaurav 26 studied the mechanical and thermomechanical properties of GFRE composites filled with multiwall carbon nanotubes (MWCNTs) (0.5, 1.0, 1.5, 2 wt.%). They concluded that the addition of MWCNTs up to 1.5 wt.% facilitates enhancement in tensile strength and glass transition temperature.…”
Section: Introductionmentioning
confidence: 99%